Ultrasound elastography in children - nice to have for scientific studies or arrived in clinical routine? - Hans-Joachim Mentzel; Katja Glutig; Stephanie Gräger; Paul-Christian Krüger; Matthias Waginger (SpringerOpen, 2022)
Abstract Ultrasound elastography (USE) is a modality that in addition to fundamental B-mode, Doppler, and contrast-enhanced sonography is suitable to make qualitative and quantitative statements about the stiffness of tissues. Introduced more than 20 years ago in adults, USE becomes now a diagnostic tool also in children. The aim of this paper is to describe current available techniques for USE in children. The significance for routine use in children is shown, and further interesting applications are reported.